Efficacy of a novel inactivated Lawsonia intracellularis vaccine in pigs against experimental infection and under field conditions. Issue 15 (3rd April 2019) - Jacobs, A.A.C.; Harks, F.; Hazenberg, L.; Hoeijmakers, M.J.H.; Nell, T.; Pel, S.; Segers, R.P.A.M.
Abstract: The efficacy of a novel inactivated Lawsonia intracellularis vaccine, Porcilis® Lawsonia, was compared to that of a commercially available live attenuated vaccine in three experimental vaccination-challenge studies in pigs. The efficacy of the new vaccine was further tested under field conditions on a farm with a history of acute ileitis. The novel inactivated vaccine consists of a freeze-dried antigen fraction that is dissolved just prior to use in either the adjuvant or in Porcilis® PCV M Hyo; an existing combination vaccine against porcine circovirus type 2 and Mycoplasma hyopneumoniae . The three experimental vaccination-challenge trials had a similar design and for each trial 75 piglets were used, randomly allotted to three groups of 25 piglets. The pigs were vaccinated at 4 or 5 weeks of age with either Porcilis® Lawsonia in adjuvant or in associated mixed use with Porcilis® PCV M Hyo (group 1), with the live vaccine (group 2), or left as unvaccinated controls (group 3). The pigs were challenged with virulent Lawsonia intracellularis 3, 4 or 17 weeks after vaccination. Post-challenge the pigs were evaluated for clinical signs, average daily weight gain, shedding and macroscopic as well as microscopic immuno-histological ileum lesion scores. In the field study, the mortality and key performance parameters were evaluated over a period of 8 months. The results of all three experimental vaccination-challenge trials showed that Porcilis® Lawsonia induced statistically significant protection against experimental Lawsonia intracellularis infection. This was demonstrated by lower clinical scores, improved weight gain, reduction of Lawsonia intracellularis shedding and reduction of macroscopic as well as microscopic ileum lesion scores when compared to the controls. The protection induced was superior to that of the commercially available live vaccine. In the field study, Porcilis® Lawsonia proved to be highly efficacious; reducing Lawsonia associated mortality to zero and improving key production parameters.